Efecto de la temperatura en la estabilidad de preparados farmacéuticos extemporáneos antihipertensivos de uso hospitalario a partir de productos genéricos (tabletas) - Roncal Saldaña, Segundo Félix (2007)
This research evaluates the temperature effect in the stability of extemporaneous compounding of captopril, enalapril and verapamilo, prepared itself of generic formulations of tablets. Three extemporaneous compounding formulations were elaborated containing captopril, enalapril and verapamilo active principle coming from the GENFAR laboratory using a simple syrup and methyl cellulose mixture as vehicle. Both formulations were put under tests of stability to temperatures of 5ºC (41ºF), 25ºC (77ºF), 40ºC (104.ºF) and 60ºC (140ºF ) evaluating temporary variations of the percentage of captopril, enalapril and verapamilo not degradated until the 18 days. The samples were quantified by method High performance liquid chromatography (HPLC). The speed of degradation (K0) and the time of expiration of the prepared have been considered. The percentage of medicaments surpluses at 5º, 25, 40º and 60º show significant variations. The time of expiration to 5ºC of the formulation of captopril is 29 days, enalapril is 78 and 103 verapamilo, to 25ºC 12 days for captopril. 30 enalapril and 47 verapamilo. With exhibitions to greater temperatures to 40ºC the formulations are not stable